Perancangan dan Implementasi FitSphere sebagai Aplikasi Android untuk Manajemen Keanggotaan Gym di Chain Gym - Aria Anggit Purnawan; Sulistyo Dwi Sancoko (J-INTECH ( Journal of Information and Technology), 2025)
The advancement of information technology in the digital era has driven transformation across various sectors, including the fitness industry. Chain Gym, a fitness center located in Klaten, faces challenges in managing data and membership services, which are still handled manually and separately. The lack of an integrated system has led to inefficiencies in processes such as class registration, fitness progress monitoring, and member information management, thereby affecting service quality and member satisfaction.This study designs and develops a mobile-based Android application named FitSphere, built using the Kotlin programming language with Firebase as the backend, to serve as an integrated platform supporting membership management at Chain Gym. The development process adopts the Rapid Application Development (RAD) methodology, which includes several stages: requirements planning through observation and interviews, system design using UML models and table relationship diagrams, construction involving coding and system integration, and the cutover phase that encompasses testing and deployment of the application.The application is equipped with key features such as membership registration, gym-related news, membership subscription, consultation, workout history, class registration, and Body Mass Index (BMI) calculation. The use of the RAD approach enables a faster and more adaptive development process that accommodates user needs and feedback.The results show that the features in FitSphere function as intended and have the potential to improve operational efficiency, making it easier for members to access services. Black Box Testing conducted on both member and admin features showed a 100% success rate, confirming that all functionalities operate correctly. The application also provides strategic benefits for management by offering deeper insights into user needs. Overall, the implementation of this application delivers an effective digital solution that enhances Chain Gym’s competitiveness in the rapidly growing fitness industry.